Hospitalized Children: Anxiety, Coping Strategies, and Pretend Play - Delvecchio, Elisa; Salcuni, Silvia; Lis, Adriana; Germani, Alessandro; Di Riso, Daniela (Frontiers in Public Health, 2019)
The aim of this paper was to assess strengths and fragilities in children aged 6 to 10 who suffered one or more hospitalizations. State and trait anxiety, coping abilities, and cognitive and affective functioning through play were assessed using a triangulation approach. Fifty hospitalized children aged 6–10 were compared to 50 non-hospitalized children, and children at first admission were compared with children with more than one hospitalization experience. The State-Trait Anxiety Scales Inventory for Children was administered for assessing trait and state anxiety, and the Children's Coping Strategies Checklist (Revision 1) was administered to assess coping dimensions. The Affect in Play Scale - Preschool - Brief (Extended version) was used to assess cognitive and affective dimensions of play. No significant differences were found for trait anxiety between hospitalized vs. non-hospitalized children. Instead, as expected, state anxiety was significantly higher in hospitalized childen than in the non-hospitalized children. Hospitalized children reported higher scores than non-hospitalized children in support-seeking strategies. As for pretend play, hospitalized children showed significantly higher cognitive scores than non-hospitalized children. However, hospitalized children appeared significantly more restricted in their affect expressions. No significant differences were found for play and anxiety scores between children admitted for the first time in the hospital ward and children with more than one admission. However, children at first admission scored higher in coping and positive cognitive restructuring and in avoidance-coping strategies than children with more than one admission. The initial assessment of the interplay of key variables such as anxiety, coping and play can inform healthcare professionals by serving as a guide in order to determine a child's risk for negative psychological outcomes due to hospitalization, to plan appropriate interventions and to provide substantial assistance to hospitalized children in the future.